Mental health assessment using Power BI: Development and application of a dashboard for companies - Aguirre y Hernández, Fernando; Méndez García, Víctor; Romero Flores, Edna Araceli; Cabrera Zepeda, Gabriela; Arrioja Carrera, Guillermo Alfredo; Romero Montoya, Mauricio (Arandu UTIC, 2025)
This study focused on the creation and application of a mental health dashboard using Microsoft Power BI and the DASS-21 scale to assess levels of stress, anxiety, and depression in two companies: a productive one and a service one. The implemented methodology comprised three main phases: the creation of Google Forms to collect data, the execution of the ETL process in Power BI, and the configuration of the dashboard. The results showed that the levels of stress, anxiety, and depression in both organizations were mostly within normal parameters. However, specific working areas and employees with critical levels of these disorders were identified, providing each company with the information necessary to take appropriate measures. The analysis by working areas revealed significant differences between departments, highlighting the importance of adapting wellness strategies to the specific needs of each section. The use of the Power BI dashboard proved to be an effective tool not only for general monitoring but also for the precise identification of risk areas and the application of preventive and corrective measures.